2021
DOI: 10.1016/j.neuroimage.2021.118489
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural properties within the amygdala and affiliated white matter tracts across adolescence

Abstract: The amygdala is a heterogenous set of nuclei with widespread cortical connections that continues to develop postnatally with vital implications for emotional regulation. Using high-resolution anatomical and multi-shell diffusion MRI in conjunction with novel amygdala segmentation, cutting-edge tractography, and Neurite Orientation Dispersion and Density (NODDI) methods, the goal of the current study was to characterize age associations with microstructural properties of amygdala subnuclei and amygdala-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…Increases in the total numbers of neurons in neighboring nuclei might still occur, but as the result of displacement of PL neurons through non-migratory means like the growth of other nearby cells. This is consistent with increases in neurite density (including axons and dendrites) measured between 8 and 22 years old in the human BLVPL discussed in Section 3.2 ( Azad et al, 2021 ). Additionally, the number of oligodendrocytes also increases throughout the amygdala in macaques, which may also account for volumetric increases in individual subnuclei ( Chareyron et al, 2012 ).…”
Section: Developmental Processes In the Plsupporting
confidence: 89%
See 3 more Smart Citations
“…Increases in the total numbers of neurons in neighboring nuclei might still occur, but as the result of displacement of PL neurons through non-migratory means like the growth of other nearby cells. This is consistent with increases in neurite density (including axons and dendrites) measured between 8 and 22 years old in the human BLVPL discussed in Section 3.2 ( Azad et al, 2021 ). Additionally, the number of oligodendrocytes also increases throughout the amygdala in macaques, which may also account for volumetric increases in individual subnuclei ( Chareyron et al, 2012 ).…”
Section: Developmental Processes In the Plsupporting
confidence: 89%
“…The volume of the BLVPL decreased in boys, but remained unchanged in girls, a change that was more strongly associated with chronological age than pubertal stage ( Campbell et al, 2021 ). The same segmentation of BLVPL also shows that the density of neurites (axons and dendrites) increases in this region between 8 and 22 years of age in both boys and girls ( Azad et al, 2021 ). It is presently unknown how decreased volume alongside increased density of neuropil relate to the changes in cellular density and neuronal maturation in the PL, and the implications of these findings for sex-specific development of the PL.…”
Section: The Paralaminar Nucleus Of the Amygdalamentioning
confidence: 65%
See 2 more Smart Citations
“…Thus, the amygdalofugal pathway may be a promising candidate neural mechanism underlying the relationship between childhood threat and amygdala-sgACC connectivity found here. Further, a recent study showed greater neurite density within the ventral amygdalofugal pathway with age, perhaps indicating greater fiber packing density and/or myelination of the tract ( Azad et al, 2021 ). Future work will be needed to examine childhood adversity-related microstructural differences within this pathway across development and to determine its multimodal relationship to functional connectivity among these ROIs.…”
Section: Discussionmentioning
confidence: 99%